The Canadian Northwest in 1811: a study in the historical geography of the old northwest of the fur trade on the eve of the first agricultural settlement - Ross, Eric DeWitt (The University of Edinburgh, 1962)
The fur traders of 1811 saw the Northwest as three distinct regions: New South Wales [Hudson Bay Lowlands], the Stony Region [C'anadian Shield] and the Great [Interiorj Plains. To them, the least important of these was New South Wales which was by then functioning primarily as a base from which the Hudson's Bay Company conducted its trade in the Northwest. It was relatively poor in both furs and provisions. Except for migrating ducks and geese, game was both scarce and unpredictable and the three factories maintained there by the company were largely dependent upon provisions from Europe and pemmican from the interior. Apart from the forested margin along its western edge, particularly in the Lake Athabasca area, the Stony Region had always been relatively poor in furs and provisions but, by 1811, it was becoming so hunted out that it was coming to be regarded as more of a barrier than as a productive region in itself - a barrier which had to be crossed to reach the rich provision areas of the grasslands and fur countries of the northern plains. Many of the natives of this area, taking advantage of their geographical position, became "middlemen" and carried the furs and provisions of wealthier countries across their homeland to trade on Hudson Bay. The broken rivers of the Stony Region added to its barrier- like appearance. navigable, river and Mackenzie. In sharp contrast were the three large, highly systems of the Great Plains, the Red, Saskatchewan, These not only enabled the traders to exploit the furs and provisions of the Great Plains but also the fur lands along the western margin of the Stony Region. Two important routes enabled the traders to cross the Stony Region to enter the rivers of the Great Plains. One led from Fort William to Lake Winnipeg and the other from York Factory to Lake Winnipeg. Each was approached from one of the two great waterways which led from the Atlantic into the heart of North America, the Saint Lawrence - Great Lakes system and Hudson Strait and Bay. By 1811, each entrance ...